SOURCES OF SELF-EFFICACY INFLUENCING ENGLISH SPEAKING SKILLS OF EFL LEARNERS - Rahmi Rahmi; Intan Raihana (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2025)
Self-efficacy is a crucial factor in English language learning because it can support students’ performance. This study aims to investigate the sources of self-efficacy influencing the speaking skills of EFL students. This research was carried out at a university in Aceh province, Indonesia. This study used a qualitative approach and involved four EFL teaching program students who completed a public speaking class as participants. The data were collected through semi-structured interviews, which were analyzed qualitatively through three concurrent flows of activity, including data condensation/reduction, data display, and conclusion drawing/verification. Bandura's (1997) theory was used to categorize the sources of the students' self-efficacy. The results show that four sources of self-efficacy had a role in shaping the EFL students' performance in speaking, including their mastery experiences, such as working as reporters and presenting in front of their peers; their vicarious experiences from local and online contexts; their psychological states; and verbal persuasions that they got from parents, friends, and lecturers.